Football is not `a matter of life and death`. It is far less important than that. Football and the COVID-19 pandemic in England - Moore, K. (Soccer & Society, 2020)
Football is currently given a significance it just does not deserve. To many fans now, it seems to have an obsessional, unhealthy importance. The current Covid-19 pandemic is an opportunity to gain a renewed perspective on football. It is just a game. We can easily live without it - if we have to. During the Second World War, for example, professional league football stopped in England for seven years. The current disruption of the game may enable us to see and value the game in a different, healthier way. This commentary explores the impact of Covid-19 on the game in England, in part by using a historical perspective, drawing upon events which have significantly disrupted the game in the country in the past. To put events in England in a wider perspective, I also then include some reflections on the impact of Covid-19, other pandemics and other events, which have disrupted football around the world.